2021
DOI: 10.3390/molecules26144208
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Molecular Structure of Constituents and Liquid Phase Non-Ideality on the Viscosity of Deep Eutectic Solvents

Abstract: Hydrophobic deep eutectic solvents (DES) have recently been used as green alternatives to conventional solvents in several applications. In addition to their tunable melting temperature, the viscosity of DES can be optimized by selecting the constituents and molar ratio. This study examined the viscosity of 14 eutectic systems formed by natural substances over a wide range of temperatures and compositions. The eutectic systems in this study were classified as ideal or non-ideal based on their solid–liquid equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…It is worth mentioning that a glass transition at 217 K was observed for samples with x thymol = 0.75 and 0.70 prepared by slow crystallization (the DSC curves are shown in Figure S2 in the Supporting Information). This can be attributed to incomplete crystallization in the samples with a lower thymol content prepared by the slow crystallization method due to their high viscosity …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth mentioning that a glass transition at 217 K was observed for samples with x thymol = 0.75 and 0.70 prepared by slow crystallization (the DSC curves are shown in Figure S2 in the Supporting Information). This can be attributed to incomplete crystallization in the samples with a lower thymol content prepared by the slow crystallization method due to their high viscosity …”
Section: Resultsmentioning
confidence: 99%
“…In the following, the second part of the phase diagram in the l -menthol-rich region, i.e., x thymol ≤ 0.67, is discussed. As already mentioned, it was impossible to crystallize the l -menthol-rich samples by slow crystallization due to the high viscosity of the mixture close to its melting temperature . Therefore, only the second preparation method, i.e., rapid crystallization, was considered.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is desirable to have L-menthol as a DES constituent. First, the activity coefficients of CO 2 at infinite dilution were calculated using COSMO-RS in pure constituents at 293.15 K because the physicochemical properties of pure constituents influence the physicochemical properties of DES ( Alhadid et al, 2021b ), and the results are shown in Figure 1 . As COSMO-RS is based on quantum mechanical calculations, the calculated activity coefficients implicitly include the atomistic rationalization and quantify the intermolecular interactions between CO 2 and the constituents in the liquid phase.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, hydrophobic DES based on natural and inexpensive nonionic constituents has attracted much attention ( van Osch et al, 2019 ). Hydrophobic DES containing L-menthol possess outstanding properties, such as low viscosity and eutectic temperatures, especially when L-menthol is mixed with phenolic alcohols, such as thymol or carvacrol ( Alhadid et al, 2020a ; Alhadid et al, 2020b ; Alhadid et al, 2021a ; Alhadid et al, 2021b ). Phenolic IL are good solvents for CO 2 capture applications ( Vafaeezadeh et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%